Democratic Republic of the Congo : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2007)
This paper presents an overview of the Poverty Reduction and Growth Strategy Paper (PRGSP) for the Democratic Republic of the Congo (DRC). The process of preparing the final PRGSP was complicated and laborious, but the government insisted that it be carried out rigorously and systematically. The objective pursued was to have a high-quality PRGSP, the contents of which were assimilated, internalized, and legitimized by all stakeholders working in a responsible partnership. Implementation of the PRGSP is subject to both endogenous and exogenous constraints.